Ethics and organizational leadership developing a normative model - Fryer, Mick. (Oxford : Oxford University Press, 2011)
By connecting theories of leadership and business ethics with moral philosophy and empirical research, this book sets out to develop an understanding of what comprises ethical leadership and to envisage a practicable model for contemporary organizations.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Leadership -- Moral and ethical aspects; Business ethics; Normativity (Ethics)